Forensic speaker comparison of Spanish twins and non-twin siblings : A phonetic-acoustic analysis of formant trajectories in vocalic sequences, glottal source parameters and cepstral characteristics - Segundo Fernández, Eugenia San (Language and Law / Linguagem e Direito, 2017)
.